1982
DOI: 10.1172/jci110708
|View full text |Cite
|
Sign up to set email alerts
|

Somatotroph Hyperplasia

Abstract: A B S T R A CT A 21-yr-old woman with Turner's syndrome presented with signs and symptoms of acromegaly. The serum growth hormone (GH) (95±9.4 ng/ ml; mean±SEM) and somatomedin C (11 U/ml) levels were elevated, and an increase in GH levels after glucose instead of normal suppression, increase after thyrotropin-releasing hormone (TRH) administration instead of no change, and decrease after dopamine administration instead of stimulation were observed. The pituitary fossa volume was greater than normal (1,440 mm3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…A stimulatory effect of GRF on somatotroph proliferation could explain the pituitary hyperplasia observed in patients with GRF-producing tumors (9)(10)(11)(12)21). In addition, it has been observed in a number of patients that the presence of neuronal tumors containing GRF immunoreactivity is associated with pituitary somatotroph adenomas and acromegaly (9).…”
Section: Resultsmentioning
confidence: 99%
“…A stimulatory effect of GRF on somatotroph proliferation could explain the pituitary hyperplasia observed in patients with GRF-producing tumors (9)(10)(11)(12)21). In addition, it has been observed in a number of patients that the presence of neuronal tumors containing GRF immunoreactivity is associated with pituitary somatotroph adenomas and acromegaly (9).…”
Section: Resultsmentioning
confidence: 99%
“…G rowth hormone-releasing hormone (GHRH), also known as growth hormone-releasing factor, was initially isolated from pancreatic tumors causing acromegaly (1,2), and hypothalamic human GHRH was shown to be identical to the one isolated from the pancreas tumor (3). Thereafter, the sequences of GHRHs were determined in various vertebrate species and in protochordates (4).…”
mentioning
confidence: 99%
“…Many investigators have reported the presence of GH-releasing activity in human carcinoid tumors (13)(14)(15) and pancreatic islet cell tumors removed from patients with acromegaly (15)(16)(17). Recently, human pancreatic GRF (hpGRF) was isolated and structurally characterized from two pancreatic islet cell tumors in patients with acromegaly (9,18,19).…”
mentioning
confidence: 99%
“…In addition, the NH2-terminal 29 amino acids of hpGRF maintain full intrinsic activity and potency in vitro (18), and recently amino acids [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] tion was stirred on a rotary mixer for 1 hr at room temperature, then dialyzed in spectapor 3 membrane tubing (Spectrum Medical Industries, Los Angeles) against a 1-liter 10 mM phosphate buffer (pH 7.4) for 2 hr at room temperature with constant stirring. The dialyzed complexes were emulsified with complete Freund's adjuvant (GIBCO) and normal saline (1:1:1) in the presence of 10 mg of active charcoal (Fisher), using two glass syringes connected by a three-way stopcock until the emulsion was firm.…”
mentioning
confidence: 99%